Effectiveness of TikTok-assisted Learning Supplement to Improve Students' Concept Understanding Ability and Learning Interest - Maulana, Muhammad Azril Rizky; Setialesmana, Depi; Yulianto, Eko (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
The use of social media such as TikTok in mathematics education and row and sequence materials is still rarely explored, although it has the potential to change the paradigm of presenting supplementary materials. This is because generally additional material is presented through platforms that are specifically for learning such as Geogebra, learning modules, or Kahoot. This study aims to determine the effectiveness of TikTok-assisted learning supplements on the ability to understand concepts and students' interest in learning the material of arithmetic rows and series from the results of test work and questionnaires through pre-test and post-test that have been carried out. The population in this study were all students of class XI SMA Negeri 1 Manonjaya and the sample in this study were students of class XI IPA 5 SMA Negeri 1 Manonjaya. This study uses a quantitative approach with quasi-experimental research methods. The results of this study, namely: 1) the use of TikTok-assisted learning supplements is effective to improve students' concept understanding ability on the material of arithmetic rows and series; and 2) the use of TikTok-assisted learning supplements is not effective to increase students' interest in learning on the material of arithmetic rows and series. The use of TikTok-assisted learning supplements is said to be effective if there is a significant difference and an increase in the average value of N-Gain (normalized gain) of concept understanding ability and students' interest in learning in the experimental class is significantly better than the control class. For this reason, other research is needed regarding the effectiveness of a social media in the context of learning on the ability to understand concepts and students' interest in learning by using other social media and/or other cognitive aspects or affective aspects. Penggunaan media sosial seperti TikTok dalam pendidikan matematika dan materi barisan dan deret masih jarang dieksplorasi, meskipun memiliki potensi untuk mengubah paradigma penyajian materi tambahan. Hal ini karena umumnya materi tambahan disajikan melalui platform yang khusus untuk pembelajaran seperti Geogebra, modul pembelajaran, atau Kahoot. Penelitian ini bertujuan untuk mengetahui efektivitas suplemen pembelajaran berbantuan TikTok terhadap kemampuan pemahaman konsep dan minat belajar peserta didik pada materi barisan dan deret aritmetika dari hasil pengerjaan tes dan kuesioner melalui pre-test dan post-test yang telah dilaksanakan. Populasi dalam penelitian ini yaitu seluruh peserta didik kelas XI SMA Negeri 1 Manonjaya dan sampel dalam penelitian ini yaitu peserta didik kelas XI IPA 5 SMA Negeri 1 Manonjaya. Penelitian ini menggunakan pendekatan kuantitatif dengan metode penelitian kuasi eksperimen. Hasil dari penelitian ini, yaitu: 1) penggunaan suplemen pembelajaran berbantuan TikTok efektif untuk meningkatkan kemampuan pemahaman konsep peserta didik pada materi barisan dan deret aritmetika; dan 2) penggunaan suplemen pembelajaran berbantuan TikTok tidak efektif untuk meningkatkan minat belajar peserta didik pada materi barisan dan deret aritmetika. Penggunaan suplemen pembelajaran berbantuan TikTok dikatakan efektif apabila terdapat perbedaan yang signifikan dan peningkatan nilai rata-rata N-Gain (gain ternormalisasi) kemampuan pemahaman konsep maupun minat belajar peserta didik pada kelas eksperimen lebih baik secara signifikan dibandingkan kelas kontrol. Untuk itu, diperlukan penelitian lain mengenai efektivitas suatu media sosial dalam konteks pembelajaran terhadap kemampuan pemahaman konsep dan minat belajar peserta didik dengan menggunakan media sosial lain dan/atau aspek kognitif atau aspek afektif lain.